Jeremy Bender vs. the Cupcake Cadets - Luper, Eric. (New York, N.Y. : Balzer + Bray, 2011)
When sixth-grader Jeremy Bender damages his father's prized boat and needs to come up with a lot of money to get it repaired, he and his best friend dress up as girls and infiltrate the Cupcake Cadet troop in an attempt to win the Windjammer Whirl model sailboat contest, and the prize money that comes with it.
MSBA Nominee 2012-13.
Keywords: Boats and boating -- Juvenile fiction; Money-making projects for children -- Juvenile fiction; Contests -- Juvenile fiction; Scouting (Youth activity) -- Juvenile fiction; Sex role -- Juvenile fiction; Humorous stories